2019
DOI: 10.3892/etm.2019.7213
|View full text |Cite
|
Sign up to set email alerts
|

miR‑212 regulated by HIF‑1α promotes the progression of pancreatic cancer

Abstract: MicroRNA-212 (miR-212) is dysregulated in numerous tissues and cancer types and serves a role in the progression of human cancer. However, the function and mechanism of miR-212 in the development of pancreatic ductal adenocarcinoma (PDAC) remain unknown, particularly in a hypoxic microenvironment. In the present study, miR-212 expression was observed to be significantly upregulated in PDAC tissues compared with normal tissues. Clinical data analysis indicated that miR-212 was positively associated with a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Similarly, the present study revealed that miR-519 was modulated by hypoxia. Certain research groups have demonstrated that various miRNAs, including miR-212 and miR-224, promote pancreatic cancer progression via hypoxia-inducible factor 1α (27,28). By contrast, the present study revealed that miR-519 inhibited the tumorigenesis of pancreatic cancer cells, in accordance with prior conclusions (29,30).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the present study revealed that miR-519 was modulated by hypoxia. Certain research groups have demonstrated that various miRNAs, including miR-212 and miR-224, promote pancreatic cancer progression via hypoxia-inducible factor 1α (27,28). By contrast, the present study revealed that miR-519 inhibited the tumorigenesis of pancreatic cancer cells, in accordance with prior conclusions (29,30).…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, it has been shown the positive correlation between deregulation of miR-212 and TNM stage, lymph node metastasis, vessel invasion, size of the tumor and the overall survival time. Latest, it has been found that in hypoxic conditions miR-212 aberration was correlated with the hypoxia-inducible factor (HIF-1α) in vivo and in vitro [ 133 ]. In turn, in cervical cancer tissues and cell lines, miR-212 was found outstandingly down regulated and promoted proliferation and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the positive relationship between the expression of HIF-1α and miR-212 in hypoxic conditions. Mechanistically, HIF-1α binds to an HRE in the miR-212 promoter region, leading to activated miR-212 expression in PC cells, and increased miR-212 was associated with a poor clinical prognosis ( 38 ).…”
Section: Non-coding Rna and Hypoxiamentioning
confidence: 99%